Performance evaluation of cellulose nanofiber with residual hemicellulose as a nanofiller in polypropylene-based nanocomposite - Norrrahim, Mohd Nor Faiz; Ariffin, Hidayah; Tengku Yasim Anuar, Tengku Arisyah; Hassan, Mohd Ali; Ibrahim, Nor Azowa; Wan Yunus, Wan Md Zin; Nishida, Haruo (MDPI AG, 2021)
Residual hemicellulose could enhance cellulose nanofiber (CNF) processing as it impedes the agglomeration of the nanocellulose fibrils and contributes to complete nanofibrillation within a shorter period of time. Its effect on CNF performance as a reinforcement material is unclear, and hence this study seeks to evaluate the performance of CNF in the presence of amorphous hemicellulose as a reinforcement material in a polypropylene (PP) nanocomposite. Two types of CNF were prepared: SHS-CNF, which contained about 11% hemicellulose, and KOH-CNF, with complete hemicellulose removal. Mechanical properties of the PP/SHS-CNF and PP/KOH-CNF showed an almost similar increment in tensile strength (31% and 32%) and flexural strength (28% and 29%) when 3 wt.% of CNF was incorporated in PP, indicating that hemicellulose in SHS-CNF did not affect the mechanical properties of the PP nanocomposite. The crystallinity of both PP/SHS-CNF and PP/KOH-CNF nanocomposites showed an almost similar value at 55–56%. A slight decrement in thermal stability was seen, whereby the decomposition temperature at 10% weight loss (Td10%) of PP/SHS-CNF was 6 °C lower at 381 °C compared to 387 °C for PP/KOH-CNF, which can be explained by the degradation of thermally unstable hemicellulose. The results from this study showed that the presence of some portion of hemicellulose in CNF did not affect the CNF properties, suggesting that complete hemicellulose removal may not be necessary for the preparation of CNF to be used as a reinforcement material in nanocomposites. This will lead to less harsh pretreatment for CNF preparation and, hence, a more sustainable nanocomposite can be produced.